An allosteric gating model recapitulates the biophysical properties of IK,L expressed in mouse vestibular type I hair cells - Spaiardi, Paolo (2017)
Type I and type II hair cells are the sensory receptors of the mammalian vestibular epithelia. Type I hair cells are characterized by their basolateral membrane being enveloped in a single large afferent nerve terminal, named the calyx, and by the expression of a low‐voltage‐activated outward rectifying K+ current, IK,L. The biophysical properties and molecular profile of IK,L are still largely unknown. By using the patch‐clamp whole‐cell technique, we examined the voltage‐ and time‐dependent properties of IK,L in type I hair cells of the mouse semicircular canal. We found that the biophysical properties of IK,L were affected by an unstable K+ equilibrium potential (VeqK+). Both the outward and inward K+ currents shifted VeqK+ consistent with K+ accumulation or depletion, respectively, in the extracellular space, which we attributed to a residual calyx attached to the basolateral membrane of the hair cells. We therefore optimized the hair cell dissociation protocol in order to isolate mature type I hair cells without their calyx. In these cells, the uncontaminated IK,L showed a half‐activation at –79.6 mV and a steep voltage dependence (2.8 mV). IK,L also showed complex activation and deactivation kinetics, which we faithfully reproduced by an allosteric channel gating scheme where the channel is able to open from all (five) closed states. The ‘early’ open states substantially contribute to IK,L activation at negative voltages. This study provides the first complete description of the ‘native’ biophysical properties of IK,L in adult mouse vestibular type I hair cells.